Anti‐EGFR Therapy in Small Bowel Adenocarcinoma. (7th February 2018) - Safyan, Rachael A.; Neugut, Alfred I.
Abstract : Small bowel adenocarcinoma is a rare disease occurring 50–100‐fold less often than colorectal cancer. This commentary describes similarities and differences between the two diseases and related results of recent clinical trials.